Survey on ART and IUI: legislation, regulation, funding and registries in European countries: The European IVF-monitoring Consortium (EIM) for the European Society of Human Reproduction and Embryology (ESHRE). Issue 1 (6th February 2020) - Calhaz-Jorge, C; De Geyter, C h; Kupka, M S; Wyns, C; Mocanu, E; Motrenko, T; Scaravelli, G; Smeenk, J; Vidakovic, S; Goossens, V
Abstract: STUDY QUESTION: How are ART and IUI regulated, funded and registered in European countries? SUMMARY ANSWER: Of the 43 countries performing ART and IUI in Europe, and participating in the survey, specific legislation exists in only 39 countries, public funding (also available in the 39 countries) varies across and sometimes within countries and national registries are in place in 31 countries. WHAT IS KNOWN ALREADY: Some information devoted to particular aspects of accessibility to ART and IUI is available, but most is fragmentary or out-dated. Annual reports from the European IVF-Monitoring (EIM) Consortium for ESHRE clearly mirror different approaches in European countries regarding accessibility to and efficacy of those techniques. STUDY DESIGN, SIZE, DURATION: A survey was designed using the online SurveyMonkey tool consisting of 55 questions concerning three domains—legal, funding and registry. Answers refer to the countries' situation on 31 December 2018. PARTICIPANTS/MATERIALS, SETTINGS, METHODS: All members of EIM plus representatives of countries not yet members of the Consortium were invited to participate. Answers received were checked, and initial responders were asked to address unclear answers and to provide any additional information they considered important. Tables of individual countries resulting from the consolidated data were then sent to members of the Committee of National Representatives of ESHRE, asking for a second check. Conflicting information was clarified by direct contact. MAIN RESULTS AND THE ROLE OF CHANCE: Information was received from 43 out of the 44 European countries where ART and IUI are performed. Thirty-nine countries reported specific legislation on ART, and artificial insemination was considered an ART technique in 35 of them. Accessibility is limited to infertile couples in 11 of the 43 countries. A total of 30 countries offer treatments to single women and 18 to female couples. In five countries ART and IUI are permitted for treatment of all patient groups, being infertile couples, single women and same sex couples, male and female. Use of donated sperm is allowed in 41 countries, egg donation in 38, the simultaneous donation of sperm and egg in 32 and embryo donation in 29. Preimplantation genetic testing (PGT) for monogenic disorders or structural rearrangements is not allowed in two countries, and PGT for aneuploidy is not allowed in 11; surrogacy is accepted in 16 countries. With the exception of marital/sexual situation, female age is the most frequently reported limiting criteria for legal access to ART—minimal age is usually set at : 18 years and maximum ranging from 45 to 51 years with some countries not using numeric definition. Male maximum age is set in very few countries. Where permitted, age is frequently a limiting criterion for third-party donors (male maximum age 35 to 55 years; female maximum age 34 to 38 years). Other legal constraints in third-party donation are the number of children born from the same donor (in some countries, number of families with children from the same donor) and, in 10 countries, a maximum number of egg donations. How countries deal with the anonymity is diverse—strict anonymity, anonymity just for the recipients (not for children when reaching legal adulthood age), mixed system (anonymous and non-anonymous donations) and strict non-anonymity. Public funding systems are extremely variable. Four countries provide no financial assistance to patients. Limits to the provision of funding are defined in all the others i.e. age (female maximum age is the most used), existence of previous children, maximum number of treatments publicly supported and techniques not entitled for funding. In a few countries, reimbursement is linked to a clinical policy. The definition of the type of expenses covered within an IVF/ICSI cycle, up to what limit and the proportion of out-of-pocket costs for patients is also extremely dissimilar. National registries of ART and IUI are in place in 31 out of the 43 countries contributing to the survey, and a registry of donors exists in 18 of them. LIMITATIONS, REASONS FOR CAUTION: The responses were provided by well-informed and committed individuals and submitted to double checking. Since no formal validation was in place, possible inaccuracies cannot be excluded. Also, results are a cross section in time and ART and IUI legislations within European countries undergo continuous evolution. Finally, several domains of ART activity were deliberately left out of the scope of this ESHRE survey. WIDER IMPLICATIONS OF THE FINDINGS: Results of this survey offer a detailed view of the ART and IUI situation in European countries. It provides updated and extensive answers to many relevant questions related to ART usage at national level and could be used by institutions and policymakers in planning services at both national and European levels. Study funding/competing interest(s): The study has no external funding, and all costs were covered by ESHRE. There were no competing interests. ESHRE Pages are not externally peer reviewed. This article has been approved by the Executive Committee of ESHRE.